(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Mistica dell’uguaglianza e mistica del lavoro - 2. La città armoniosa - 3. Il denaro - 4. Anticapitalismo mistico e tradimento della fraternità. Labor, remuneration and rights in the writings of Charles Péguy: suggestions and reflections for the canonist ABSTRACT: Both in "Marcel: premier dialogue de la cité harmonieuse" and in "L’argent", Charles Péguy creates an aesthetic of work that emphasizes the fundamental relationship between the creative activity of man, spirituality and fraternity. Manual labor is at the same time an instrument of creation of the social bond and the fulcrum of the connection between the temporal element and the spiritual one. At the same time, Péguy appears very critical of the commodification of labor in capitalist society, where money is not a mere tool for exchange but an economic goal in itself. The dignity of work and respect for the principle of fraternity are today in question following the recent reforms of the Italian labor legislation; reforms that seem far removed from the perspective outlined in the writings of Charles Péguy.